Implementasi Projek Penguatan Profil Pelajar Pancasila dengan Pengenalan Wirausaha Dampo Pisang di Kelas IV SD Negeri 117 Inpres Kurusumange Kabupaten Maros - Islamiyyah, Islamiyyah; Hastati, Sri; Erniati, Erniati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
Abstract: The research aims to find out: (1) the implementation process of the Pancasila Student Profile Strengthening Project with the introduction of banana dampo entrepreneurs, (2) the obstacles that arise in the implementation of the Pancasila Student Profile Strengthening Project with the introduction of banana dampo entrepreneurs, and (3) the values that are grown/arisen in the Pancasila Student Profile Strengthening Project with the introduction of banana dampo entrepreneurs. The type of research conducted is qualitative research. Data collection techniques are carried out by means of observation, interviews and documentation. The results of the research and data analysis conducted show that the implementation of P5 with the introduction of banana dampo entrepreneurs has been carried out starting from the introduction, contextual, action as well as reflection and follow-up stages. The obstacles faced by teachers in P5 can be overcome by inviting students to carry out entrepreneurial activities in a simpler way. Through the introduction of Dampo Pisang entrepreneurship in P5, students can foster an entrepreneurial spirit in students. Keywords: Strengthening Pancasila Student Profile, Entrepreneurship, Banana Dampo.